Assessing innovation in transport: An application of the Technology Adoption (TechAdo) model to Maritime Autonomous Surface Ships (MASS). (December 2021) - Fonseca, Tiago; Lagdami, Khanssa; Schröder-Hinrichs, Jens-Uwe
Abstract: Maritime autonomous surface ships (MASS) have received significant attention recently both by academia and industry to the point that the International Maritime Organization (IMO) started a regulatory scoping exercise. So far, most of the discussions have been solely focused on technical developments, thus overlooking the complex array of socio-economic and policy factors. This paper aims to fill this gap by comprehensively analyzing MASS development. We develop and apply a novel model of technology adoption (TechAdo) to holistically assess MASS as an innovation. By triangulating data from elite interviews, with work at the IMO and a systematic literature search, we show that MASS is in development but still in its infancy. Our analyses show that factors in the enabling environment (social acceptance, regulation, and governance), along with human capital, have been overlooked and need to be carefully considered by future research and policy. Highlights: The TechAdo model is proposed and validated to assess transport innovation. MASS is in its infancy, as technical issues dominate its developments. MASS is more attractive to short-distance shipping and coastal segments. Shipowners have limited interest in MASS, but vendors push for MASS innovation. We critical identify and discuss the possible MASS champions. Misalignment between buyers and sellers is likely to be solved in the policy area.